1995
DOI: 10.1016/0735-1097(95)96225-n
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II inhibits the forearm vascular response to increased arterial pressure in humans

Abstract: Both pressor and nonpressor infusions of angiotensin II immediately inhibit the forearm vascular response to mild baroreflex loading in normal humans. If present over the long term, such effects could contribute to inappropriate peripheral resistance in diseases such as hypertension and congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…16 Our results also verify the apparent divergence in the scientific literature that includes credible descriptions of both stimulatory 1,3,[17][18][19] and suppressive effects 5,8,20 of AII on the sympathetic nervous system. Finally, the enhancement of AII-dependent neuronal stimulation in the presence of the L-channel blocker nifedipine is consistent with the sympathoexcitation seen during long-term use of this agent in humans 21 and may help explain the potential adverse effects observed with calcium antagonists in high-risk patients.…”
Section: Discussionsupporting
confidence: 72%
“…16 Our results also verify the apparent divergence in the scientific literature that includes credible descriptions of both stimulatory 1,3,[17][18][19] and suppressive effects 5,8,20 of AII on the sympathetic nervous system. Finally, the enhancement of AII-dependent neuronal stimulation in the presence of the L-channel blocker nifedipine is consistent with the sympathoexcitation seen during long-term use of this agent in humans 21 and may help explain the potential adverse effects observed with calcium antagonists in high-risk patients.…”
Section: Discussionsupporting
confidence: 72%
“…Thus 3 weeks of treatment with losartan in hypertensive patients resulted in a significant fall in blood pressure, but no significant changes in heart rate or HRV in the frequency domain, although cross-spectral analysis showed that BRS was significantly increased with losartan [25]. In humans, our studies have shown that cardiac vagal control is reduced by angiotensin II [3], and a facilitatory action on the baroreflex control of sympathetic activity has also been described [27]. The consistent lack of effect of AT " receptor antagonists on measures of cardiac autonomic control in humans might be considered surprising in view of the well described actions of angiotensin II and the results of studies with ACE inhibitors.…”
Section: Discussionmentioning
confidence: 58%
“…Central and peripheral actions resulting in inhibition of cardiac parasympathetic control and facilitation of sympathetic activity have been demonstrated in animals [6][7][8]. In humans, our studies have shown that cardiac vagal control is reduced by angiotensin II [3], and a facilitatory action on the baroreflex control of sympathetic activity has also been described [27]. These actions appear to be mediated by AT " receptors [28], and therefore pharmacological blockade might be expected to increase measures of cardiac vagal activity and reduce those related to sympathetic activity.…”
Section: Discussionmentioning
confidence: 52%